2014
DOI: 10.1051/0004-6361/201323325
|View full text |Cite
|
Sign up to set email alerts
|

Local stability of a gravitating filament: a dispersion relation

Abstract: Filamentary structures are ubiquitous in astrophysics and are observed at various scales. On a cosmological scale, matter is usually distributed along filaments, and filaments are also typical features of the interstellar medium. Within a cosmic filament, matter can contract and form galaxies, whereas an interstellar gas filament can clump into a series of bead-like structures that can then turn into stars. To investigate the growth of such instabilities, we derive a local dispersion relation for an idealized … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 81 publications
4
31
0
Order By: Relevance
“…Then in the limit of r → r flat , Equation (14) Freundlich, Jog, & Combes (2014). We also note that a Plummer-like profile (p = 2), fits the radial density distribution of the post-collapse filament very well when gas temperature is calculated by accounting for gascooling.…”
Section: Stability Of Filaments In Star-forming Clouds and The Formatmentioning
confidence: 61%
See 1 more Smart Citation
“…Then in the limit of r → r flat , Equation (14) Freundlich, Jog, & Combes (2014). We also note that a Plummer-like profile (p = 2), fits the radial density distribution of the post-collapse filament very well when gas temperature is calculated by accounting for gascooling.…”
Section: Stability Of Filaments In Star-forming Clouds and The Formatmentioning
confidence: 61%
“…Freundlich, Jog, & Combes (2014) derived a dispersion relation for a rotating non-magnetised filamentary cloud idealised as a polytropic cylinder with localised density perturbations. Under these simplifying assumptions, the authors demonstrated that the filament indeed developed Jeans-type instability with propensity to fragment on the scale of the local Jeans length.…”
Section: Anathpindika and Freundlichmentioning
confidence: 99%
“…Studies that consider deviations from isothermality include Goldreich & Lynden-Bell (1965) who obtained stability criteria for pressure bounded, uniformly rotating polytropic sheets. The fragmentation of cylindrical filaments was first studied by Chandrasekhar & Fermi (1953) in the magnetized, isothermal and incompressible case and has been since then the object of careful attention of many authors including, in addition to those mentioned above, notably Ostriker (1964a), and more recently Breysse et al (2014) and Freundlich et al (2014a) for instance. Most these studies, if not all, approach the problem with the usual procedure of analyzing the system of linearized equations in the so-called primitive variables (see section 7.1.1 below).…”
Section: Spectral Theorymentioning
confidence: 99%
“…The recent observations by the Herschel Space Observatory have revealed that filaments are prevalent within molecular clouds and that star-forming cores are often embedded within them (André et al 2010;Arzoumanian et al 2013;Könyves et al 2015;Marsh et al 2016). The ubiquity of filamentary structures has lead to numerous papers studying the effects their geometry has on stability and fragmentation (Ostriker 1964;Larson 1985;Inutsuka & Miyama 1992;Freundlich, Jog & Combes 2014;Clarke, Whitworth & Hubber 2016).…”
Section: Introductionmentioning
confidence: 99%